Pathways into Creativity and Place for Adult Learning: A Dialogue Between a Researcher and an Artist - Mason, Stephanie; de Condé, Rachel (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2022)
The purpose of this article is to share how two friends approach creativity in their professional lives in research and in the arts, and what we have learned through insights into places that impact this work. Our different approaches are reflected in our positionalities: one author is an emerging arts-informed researcher and university instructor, and the other author is a practising fine arts craftsperson and part-time faculty member. Our close friendship and ongoing conversations serve to connect our approaches to working with the arts, even as our attitudes to creativity and learning are demarcated. Relayed in the form of dialogue in response to guiding questions, this article is an expansive discussion of what work in the arts can look like, and how the interplay of creativity and place afford as-yet-untapped pathways of understanding that better suit contemporary conditions of life and study.